Detection of ADB-BUTINACA Metabolites in Human Urine, Blood, Kidney and Liver. Issue 6 (3rd August 2021) - Kavanagh, Pierce; Pechnikov, Alexandr; Nikolaev, Ivan; Dowling, Geraldine; Kolosova, Mariia; Grigoryev, Andrej
Abstract: The N -butyl indazole derivative, N -(1-amino-3, 3-dimethyl-1-oxobutan-2-yl)-1-butyl-1H-indazole-3-carboxamide (ADB-BUTINACA or ADB-BINACA), currently a drug of abuse in Russia, is reported to have a cannabinoid receptor potency and efficacy almost three times higher than JWH-018. ADB-BUTINACA was detected in blood from patients with suspected drug intoxications, as well as in blood, kidney and liver samples collected during postmortem investigations. Using liquid chromatography–time-of-flight–mass spectrometry, a number of ADB-BUTINACA metabolites were tentatively identified in urine samples. These include products of mono- and dihydroxylation, hydroxylation of the N-butyl side chain and dehydrogenation, formation of a dihydrodiol, hydrolysis of the terminal amide group, N-dealkylation of the indazole and a combination of these reactions. The dihydrodiol was found to be the predominant metabolite, with its chromatographic peak area exceeding those of other metabolites by almost an order of magnitude. For the routine analysis of blood, liver and kidney samples, the dihydrodiol and monohydroxylated metabolites along with the parent compound are recommended as target analytes. The same metabolites in free and glucuronidated forms are also recommended for analytical confirmation in urine samples.